Mechanical Properties of Sustainable Paving Blocks Using Fly Ash and Polypropylene Plastic Waste - Sahputra, Deded Eka; Fakhrul Siddiq; Nanang Fatchurrohman (Faculty of Engineering and Technology, Sampoerna University, 2026)
The increasing generation of industrial and plastic waste has encouraged the development of sustainable construction materials. This study investigates the mechanical properties of zero-cement paving blocks utilizing Polypropylene (PP) plastic waste as the sole binder and fly ash as a sand substitute. A direct thermo-mechanical melting process at 180°C–200°C was employed without the use of water or chemical activators. To ensure sufficient binder volume, the PP ratio was fixed at 4 parts. Specimens were tested for compressive strength and water absorption according to the Indonesian National Standard (SNI 03-0691-1996). The results demonstrated a clear dependency between the filler ratio and mechanical performance; a 25% substitution of sand with fly ash achieved the optimal performance, yielding a maximum compressive strength of 11.59± 0.84 MPa and a remarkably low water absorption rate of 0.75 ± 0.31%, while the lowest water absorption of 0.62 ± 0.07% was achieved by the control mixture. However, increasing the fly ash substitution to 50% resulted in a strength reduction due to the inability of the fixed PP matrix to completely encapsulate the high surface area of the fine fly ash particles. Although classified as Quality D paving blocks, this purely waste-derived composite presents a highly viable, eco-friendly solution specifically targeted for light-duty infrastructure applications, such as pedestrian walkways and city parks.